Keputusan afiliasi OTA dan kinerja Hotel: Studi Pada Hotel Berafiliasi - Setiawan, Antonius Singgih; Lina, Lina (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2020)
At present, the hotel industry is at a very dynamic level of competition. The intense competition requires hotel managemet to implement the right strategy. One strategy that must be implemented is a digital marketing strategy. Digital marketing strategy is a choice of strategies that are developing at this time. However, the development of hotel marketing practices through digital marketing has not been much followed by research developments in the field of digital marketing in the hotel industry. Therefore, this study aims to prove whether the hotel's decision to implement a digital marketing strategy by affiliating with an online travel agent (OTA) will achieve better performance. The research uses exploratory quantitative methods. Using data collected from 65 respondents who are hotel owners/managers, the data is processed using descriptive statistics. The results showed that the hotel decision affiliated with OTA had a positive impact on hotel performance.